Design, Implementation and Evaluation of SDN-based Resource Management Model - Celenlioglu, Mahmud Rasih; Alsadi, Mohammed; Mantar, Haci Ali (IEEE, 2015)
Usage of the Internet has been changed over the past decade. Current tightly-coupled network architecture limits innovative actions. Besides, companies desire to provide better service while keeping their costs low. Software Defined Networking (SDN) is a new approach that provides abstract, programmable and open networking. It is brought up to address these issues. In this study1, we present the design, implementation and evaluation of pre-established multi-path (PMP) based intra-domain routing and resource management model for SDN-based networks. PMPs are established between each pair of edge nodes. Controller performs routing, admission control and resource management based on these paths. The experimental works show that the proposed model provides scalable admission control, routing and significantly improves resource utilization.
7th International Conference on New Technologies, Mobility and Security (NTMS) -- JUL 27-30, 2015 -- Paris, FRANCE